A safe microbe-based procedure for a gentle removal of aged animal glues from ancient paper. (April 2016) - Barbabietola, Nicoletta; Tasso, Flavia; Alisi, Chiara; Marconi, Paola; Perito, Brunella; Pasquariello, Giovanna; Sprocati, Anna Rosa
Abstract: In the past, the animal glues were used in paper manufacturing and in restoration of artworks preserved in museums, libraries and archives. By ageing they went through deterioration creating distortions, tensions, cockling and discolouration in paper materials. Consequently, the removal of glue residues becomes an essential step in the restoration of ancient and artwork paper material. Current mechanical and chemical methods display serious drawbacks mainly related to aggressiveness towards material or toxicity for restorers. Bio-based methods for paper cleaning rely on the use of enzymes that require skilled operators, optimal application conditions and high costs, creating difficulties in mastering enzyme use so far. This paper describes a first attempt of biocleaning ancient paper from organic deposits using living bacteria. The non-pathogenic, non-spore-forming and non-cellulolytic original strain Ochrobactrum sp. TNS15 E was successfully applied -immobilised in an agar gel-on original paper specimens dating back to the 17th. After 4 h of contact with the bacterial pack, the cellulose fibres underlying glue were disclosed, highlighting the bacterial capacity of removing the glue layer without damaging the paper or leaving undesirable residues. Both colorimetry and SEM analyses proved the results. The procedure is simple, low-cost and safe for the artefact, the restorers and the environment. Highlights: Ancient paper specimens were deteriorated by a compact layer of aged animal glue. Bacterial strains belonging to the ENEA-Lilith collection were selected as effective animal glues degraders. Living cells of Ochrobactrum sp. TNS15 E entrapped in an agar gel were applied on paper. Four hours of treatment disclosed cellulose fibres at SEM observation, without damage for paper. This is the first report on the use of living bacteria for cleaning ancient paper from animal glues.